2015
DOI: 10.1097/hcm.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Has Competition Increased Hospital Technical Efficiency?

Abstract: Hospital competition and managed care have affected the hospital industry in various ways including technical efficiency. Hospital efficiency has become an important topic, and it is important to properly measure hospital efficiency in order to evaluate the impact of policies on the hospital industry. The primary independent variable is hospital competition. By using the 2001-2004 inpatient discharge data from Florida, we calculate the degree of hospital competition in Florida for 4 years. Hospital efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
(22 reference statements)
2
18
0
Order By: Relevance
“…In addition, economic market theories predict that hospital competition will motivate hospitals to seek to improve their quality of health care delivery to attract patients . However, in the market for hospital services, it is unclear whether hospital competition enhances hospital efficiency . Some studies have found that when a hospital was located in a highly competitive market, its efficiency score was higher than the scores of hospitals in a less competitive market .…”
Section: Theoretical Foundation/conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, economic market theories predict that hospital competition will motivate hospitals to seek to improve their quality of health care delivery to attract patients . However, in the market for hospital services, it is unclear whether hospital competition enhances hospital efficiency . Some studies have found that when a hospital was located in a highly competitive market, its efficiency score was higher than the scores of hospitals in a less competitive market .…”
Section: Theoretical Foundation/conceptual Modelmentioning
confidence: 99%
“…Over the last 2 decades, US hospitals have been facing increasing external pressures to maximize their performance in providing quality care. These external pressures include expansion of managed care, market competition, public policy, number of uninsured, and shortages of health care professionals . For instance, in 2014, to decrease preventable adverse events and enhance efficiency of patient care, the Centers for Medicare and Medicaid Services (CMS) established the Hospital‐Acquired Condition Reduction program for reducing payments to the lowest‐performing hospitals .…”
Section: Introductionmentioning
confidence: 99%
“…The SE in the eastern region increased, and PTE remained high. Since the 2012 reform of county-level public hospitals, they have implemented a series of measures for their existing management systems, compensation mechanisms, personnel distribution, and cost structures [5] . Although the TE of the hospitals in the three Chinese regions declined, overall it was trending upward.…”
Section: Discussionmentioning
confidence: 99%
“…County-level public hospitals, as the leaders of China's three-tiered rural health care network, have a positive effect on the normal use of tertiary health care networks [2][3][4] . As medical institutions for the treatment of frequently occurring and common diseases, county-level public hospitals have been affected by their own efficiency in addition to objective reasons such as regional economic and social development [4][5] . If a hospital's operating efficiency is low, more government investment will fail to improve its efficacy and waste resources, exacerbate the shortage of resources, and affect patients' medical experiences.…”
Section: Introductionmentioning
confidence: 99%
“…In conventional markets, this may lead to greater efficiency; however, it is not always the case in the healthcare market [53]. A study in 2001-2004, assessing the effects of competition on efficiency among hospitals in Florida found that hospitals located in a less competitive market had lower technical efficiency scores than those in a more competitive market [54]. In contrast, research on hospital efficiency in Turkey indicates that efficiency is not significantly affected by the intensity of competition among hospitals [55].…”
Section: Competitionmentioning
confidence: 99%